The interplay between leisure, friendship, and dementia. (August 2021) - Fortune, Darla; Whyte, Colleen; Genoe, Rebecca
The ways in which friends behave can greatly influence the experience of living with dementia. For example, previous research has highlighted the negative implications that dwindling friendships have on one's leisure engagement after a diagnosis of dementia. In this study, we share findings from a study that highlights the interplay between leisure, friendship, and dementia to demonstrate the complementary relationship that can exist. Specifically, we describe ways friendship can be a bridge to maintaining leisure engagement and how leisure can, in turn, support the maintenance of friendships for individuals with dementia. Data were gathered through individual, dyad, and group interviews conducted with individuals with dementia and their friends and family. Our findings have implications for friends of individuals with dementia who may be searching for ways to support the continuation of mutually enjoyable leisure experiences. Findings also have implications for the ways leisure providers can more fully attend to the relational needs of individuals with dementia in order to help support their continued friendships.